2015
DOI: 10.1111/rda.12524
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Breeding Management and Use of Ovulation Induction for Fixed‐time AI

Abstract: ContentsThe objective of the breeding herd is the predictable and consistent production of high quality pigs. To achieve this objective, an appropriate number of females need to be mated in each breeding week and they should maintain their pregnancy and deliver large litters. Many factors can impact achievement of optimal sow productivity, particularly breeding management. Most matings will involve artificial insemination (AI), and successful AI requires deposition into the cervix (or beyond) of sufficient via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…The main aim of fixed‐time artificial insemination (FTAI) is to use a single semen dose within a period of 0–24 hr before ovulation (Nissen, Soede, Hyttel, Schmidt, & D'hoore, ; Soede, Wetzels, Zondag, De Koning, & Kemp, ). While using FTAI in swine, an ovulation time control is needed because of the highly variable interval between the oestrous onset and ovulation (Brüssow et al., ; Kirkwood & Kauffold, ). Therefore, it is necessary to use appropriate hormone doses at the right moment for manipulating the ovulation moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aim of fixed‐time artificial insemination (FTAI) is to use a single semen dose within a period of 0–24 hr before ovulation (Nissen, Soede, Hyttel, Schmidt, & D'hoore, ; Soede, Wetzels, Zondag, De Koning, & Kemp, ). While using FTAI in swine, an ovulation time control is needed because of the highly variable interval between the oestrous onset and ovulation (Brüssow et al., ; Kirkwood & Kauffold, ). Therefore, it is necessary to use appropriate hormone doses at the right moment for manipulating the ovulation moment.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadotropin‐releasing hormone (GnRH) analogues or LH/hCG (luteinising hormone/human chorionic gonadotropin) have been efficiently used to induce ovulation in weaned sows (Kirkwood & Kauffold, ). FTAI protocols following the use of porcine LH (pLH), in combination with equine chorionic gonadotropin (eCG) at weaning (Bennet‐Steward, Aramini, Pelland, & Friendship, ; Cassar, Kirkwood, Poljik, Bennett‐Steward, & Friendship, ) or a single pLH application at the onset of oestrus, have been proposed for weaned sows (Fontana et al., ; Ulguim et al., ; Zak et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the developmental status of follicles or parity could have affected the responsiveness (i.e., estrus expression) of sows treated with or without P.G. 600 in the current study as reviewed by Kirkwood and Kauffold, 2015. Perhaps P.G.…”
Section: Discussionmentioning
confidence: 92%
“…This agrees with findings from Weitze et al (1994), who reported that the duration of estrus decreased from 72 h with sows having a WEI less than 4 d to approximately 50 h when the WEI increased to 4.5 to 5 d. Additionally, the EOI also was reduced from 53 h to 39 h at a WEI of 4 to 4.5 to 5 d, respectively. Kirkwood and Kauffold (2015) reviewed the relationships between WEI, onset of estrus, and ovulation.. Sows that have a short WEI (< 4 d) tend to have a longer duration of estrus and ovulate later (late ovulators). Sows that had a longer WEI (> 5 d) tended to have a shorter duration of estrus and ovulate earlier (early ovulators).…”
Section: Timing Of Artificial Inseminationmentioning
confidence: 99%
“…Buserelin® and Goserelin® (acting at pituitary gland level). For more details, including dosage and timetable, see reviews of [18] and [19]. A protocol including porcine LH and single fixed-time AI, 36 h after porcine LH application resulted in farrowing rates of 86.1 % and 10.6 piglets born per litter, comparable to control untreated sows and double AI [20].…”
mentioning
confidence: 99%